PENERAPAN MODEL SSCS UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA SMP PADA MATERI GEOMETRI - Tralisno, Agung; Alfi, Syamiah (As-Sulthan Journal of Education, 2025)
The issue of students' insufficient performance in mathematics is a concern recognized by teachers. Consequently, educators are required to identify ways to address the challenges they encounter to enhance educational results. This study seeks to elevate the mathematics learning achievements of students. The research focuses on enhancing students' mathematics skills through a technique referred to as Search, Solve, Create, and Share (SSCS). The SSCS method consists of four phases: search phase, completion phase, innovation phase, and sharing phase. This investigation is classified as action research conducted in the eighth grade of middle school. The participants in this study comprised 30 eighth-grade pupils, with the primary emphasis on their mathematics learning performance. The process of data analysis was conducted using a qualitative descriptive method. The results of the study indicate a significant enhancement in student outcomes, beginning with an average score of 68.5 before the first cycle, which increased to 81.56 in cycle I, and then to 89.23 in cycle II. Moreover, the percentage of students reaching the success level rose from 40% to 76% in cycle I, and further to 96% in cycle II. Therefore, it can be concluded that implementing the Search, Solve, Create, and Share (SSCS) educational method has effectively improved students' learning performance.